Immobilization of lipase from Penicillium sp. section Gracilenta (CBMAI 1583) on different hydrophobic supports: Modulation of functional properties - Turati, Daniela F. M. [UNESP]; Morais, Wilson G.; Terrasan, César R. F.; Moreno-Perez, Sonia; Pessela, Benevides C.; Fernandez-Lorente, Gloria; Guisan, Jose M.; Carmona, Eleonora C. [UNESP] (MDPI, 2017)
Lipases are promising enzymes that catalyze the hydrolysis of triacylglycerol ester bonds at the oil/water interface. Apart from allowing biocatalyst reuse, immobilization can also affect enzyme structure consequently influencing its activity, selectivity, and stability. The lipase from Penicillium sp. section Gracilenta (CBMAI 1583) was successfully immobilized on supports bearing butyl, phenyl, octyl, octadecyl, and divinylbenzyl hydrophobic moieties wherein lipases were adsorbed through the highly hydrophobic opened active site. The highest activity in aqueous medium was observed for the enzyme adsorbed on octyl support, with a 150% hyperactivation regarding the soluble enzyme activity, and the highest adsorption strength was verified with the most hydrophobic support (octadecyl Sepabeads), requiring 5% Triton X-100 to desorb the enzyme from the support. Most of the derivatives presented improved properties such as higher stability to pH, temperature, and organic solvents than the covalently immobilized CNBr derivative (prepared under very mild experimental conditions and thus a reference mimicking free-enzyme behavior). A 30.8- and 46.3-fold thermostabilization was achieved in aqueous medium, respectively, by the octyl Sepharose and Toyopearl butyl derivatives at 60 °C, in relation to the CNBr derivative. The octyl- and phenyl-agarose derivatives retained 50% activity after four and seven cycles of p-nitrophenyl palmitate hydrolysis, respectively. Different derivatives exhibited different properties regarding their properties for fish oil hydrolysis in aqueous medium and ethanolysis in anhydrous medium. The most active derivative in ethanolysis of fish oil was the enzyme adsorbed on a surface covered by divinylbenzyl moieties and it was 50-fold more active than the enzyme adsorbed on octadecyl support. Despite having identical mechanisms of immobilization, different hydrophobic supports seem to promote different shapes of the adsorbed open active site of the lipase and hence different functional properties.
Keywords: Enzyme immobilization; Enzyme stabilization; Fish oil ethanolysis; Fish oil hydrolysis; Omega-3 production